NARASI CINTA DAN KEINDAHAN DALAM BAHASA SUFI IBN ARABI - Kholil, Ahmad (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2007)
Ibn Arabi is the type of the mystical-muslim philosophy. He was known as the founder of an idea â€œwahdat al-wujudâ€, and his theory explained that cosmos was created by God from its one-necleus. So, in spite of its external aspects different and has variations, its essence just one. It mind there is God attribut in cosmos, and God is the essence of its share. The common of mystical muslim coveted the â€œkasyfâ€ to understand Him, The Great Unity, God. In this case, Ibn Arabi connected it and love. Love, Ibn Arabi said, had to come into existence becaose of â€œjamalâ€, the beaty which God-loved and â€œihsanâ€, the beautiful attitude to reach love of God.